THEMATIC WORKSHOPS AS POTENTIATING OF CARE TO ELDERLY IN HOSPITAL - Juliane Elis Both; Marinês Tambara Leite; Leila Mariza Hildebrant; Ana Maria Massariol; Margrid Beuter; Mirian da Silveira Perrando (Universidade Federal de Santa Maria, 2014)
Doi: 10.5902/2179769211009 Aim: to analyze the contributions of thematic workshopsto care for hospitalized elderly, developed with nursing professionals. Method: it is a qualitative and descriptive research that has the convergent-assistance research as theoretical and methodological reference. The subjects are professionals of nursing of a medical clinic unity of a hospital located in northwest of Rio Grande do Sul. Results: through the educative practices with the professionals, it was possible to connect the to know and do, interfering positively in the praxis of care to hospitalized elderly. Final Considerations: the educational practice consists of a strategy to qualify the care with hospitalized elderly.